Answer:
-2x + 3 – (5 – 6x) = 4x - 2
Step-by-step explanation:
The given expression is :
-2x + 3 – (5 – 6x)
We need to simplify the above expression. First opening the brackets.
-2x + 3 – (5 – 6x) = -2x + 3 – 5 + 6x
Taking like terms together,
= -2x+6x + 3 -5
= 4x - 2
So, the simplified expression is 4x - 2.
I think the best answer would be F.
When √10 is converted into a decimal it is 3.16, and F is the most close to that.
Hope this helps!
Answer:
C
Step-by-step explanation:
68 - 80 / 80
= - 12 / 80
= - 3 / 20
= - 15%